Body language secrets to win more negotiations : how to read any opponent and get what you want - Williams, Greg (Public speaker); Iyer, Pat (Career Press, 2016)
The success of a negotiation is profoundly affected by how well you read body language. How can you learn to read the subtle clues many lasting a fraction of a second that your opponent projects?